Impact of Population Growth on Forest Cover: A Case Study of Tawang District of Arunachal Pradesh - Gendan Tsering; Gibji Nimasow; Nandini Chakrabarthy Singh (Dera Natung Government College Research Journal)
The role of population growth on the forest degradation has been much debated worldwide. There is a reciprocal relationship between population growth and forest cover in large. In other words, population growth turns out to be the main cause of deforestation. Deforestation threatens the well-being and livelihoods of millions of people who largely depends on forest resources. Today deforestation is occurring at alarmingly rates, especially in the regions that are experiencing rapid population growth. Tawang district of Arunachal Pradesh has a population density of 22 persons per square kilometres which is higher than the state. The district is inhabited by the Monpa tribes who are living in close association to their forest resources and derive their daily requirements like fire woods, timber, medicinal plants, food and fodder for their animal. The fire wood extraction appears to be causing maximum impact on forest degradation as firewood forms the basic source of heating the houses in an area which is characterized by longer winter months. Every year each household burns at least two fully matured trees to keep their houses warm. But there is no denying the fact that the other form of extractions are also contributing in the deforestation. Earlier, man-nature interaction was quite sustainable when population was very low. But today due to rapid population growth interaction with forest is becoming more and more intense leading to loss of many important resources. Consequently, many important plant species like rhododendron, oak, juniper pines, etc. are largely threatened. The paper attempts to examine the population growth trend in the Tawang district and and its impact on the forest cover of the district. Both the primary and secondary data sources have been used to analyse the relationship between population growth and forest cover change in the district.